PROGRAM ARTEMIS: TANTANGAN HUKUM RUANG ANGKASA DI ERA BARU - Nugraha, Taufik Rachmat (Veritas et Justitia, 2022)
Artemis program has mainly focused on space exploration and exploitation of the Moon and other celestial bodies. United States government as initiator is inviting government and non-government entities to involved in the Artemis program through Artemis Accords. Furthermore, this program will challenge Corpus Juris Spatialis as existing law. It could not properly answer the future problems because this law has begun obsolete after 50 years since it was composed. However, Corpus Juris Spatialis was too geocentric, using Earth as the primary benchmark of space activities. Because of that, it has lacunæ on mineral exploitation, space environment, and properties issues. Based on those facts, there must be a new regulation along with planetary sustainability approach and with space-centric character on which covered all future questions comprehensively. Furthermore, this article will examine the Artemis program using a comparative method between the U.S. and Luxembourg national legislation with Corpus Juris Spatialis as existing international space law. The author will propose a space-centric concept as a new approach to preserve outer space as the common heritage of mankind and reducing space environmental damage from such activities.